Genetic characterization of a unique neuroendocrine transdifferentiation prostate circulating tumor cell-derived eXplant model - Vincent Faugeroux (Nature Portfolio, 2020)
Better tumor models are needed for the neuroendocrine subtype of castration resistant prostate cancer (CRPC-NE). Here, the authors develop patient-derived model from circulating tumor cells of a CRPC-NE patient, and provide insights on the sequential acquisition of driver gene mutations promoting NE transdifferentiation.